Enhancing the Students' Speaking Achievement using the Shadowing Technique at SMKN 2 palembang - Wulan Sri Ayu Kartika Kirana; Dio Resta Permana; Nike Anggraini (Journal of English for Academic and Specific Purposes (JEASP), 2026)
This study aimed to examine the application of the shadowing technique in enhancing the speaking achievement of vocational high school students, addressing common problems such as students’ lack of self-confidence and low awareness of the importance of learning. The research employed a quasi-experimental design involving 70 students from SMKN 2 Palembang, equally divided into two groups: 35 students in the experimental group and 35 in the control group. The experimental group received shadowing instruction, while the control group had regular lessons over ten meetings with a pre-test, treatment, and post-test. Students’ opinions were collected through a questionnaire, and the results were analysed using paired and independent sample t-tests. The paired sample t-test revealed that the mean score improvement in the experimental group reached 33.26 points, while the control group showed an increase of only 13.20 points, indicating greater improvement in the group that received the shadowing treatment. Additionally, the independent sample t-test showed a mean difference of 5.321 points in the post-test scores between the experimental and control groups, suggesting that the shadowing technique significantly contributed to improved speaking achievement. The shadowing technique enhanced students’ speaking achievement and their listening achievement. Students also responded positively, with greater motivation, confident and engagement in learning.